Purchase Intention of College Students in China to H Mobile Phone during the Sino-US Trade War (International Journal of Applied Research in Management and Economics, 2020)
The purpose of this study is to investigate will college students in China still purchase H mobile phones during Sino-US trade war, most importantly is to understand what factors affect purchase intention of H mobile phone to college students in China during this special period and is there any significant difference in purchase intention among different demographic characteristics. The researcher used convenience sampling and snowball sampling to collect 386 valid data by distributing the questionnaire online in five provinces in China from 425 respondents. Cronbach’s alpha was measured to test the reliability of the data. Besides, Pearson correlation, multiple linear regression and ANOVA are used to test hypotheses. The findings revealed that more than half of college students in China will still purchase H phones and there is a significant difference in purchase intention among different genders, age groups, provinces, money respondents are willing to pay for a phone and different number of phones respondents are using at present. Most importantly, four of six independent variables have significant influence on purchase intention of H phones which are product features, social influence, and ethnocentrism and brand image. The findings of this study are limited by number of respondents and non-probability sampling method. Anyway, this study can predict to a great extent whether H mobile phone will survive this difficult time and give an answer to the world.